2023
DOI: 10.1021/acs.est.2c08004
|View full text |Cite
|
Sign up to set email alerts
|

1-Butyl-3-methylimidazolium Chloride Affects Anaerobic Digestion through Altering Organics Transformation, Cell Viability, and Microbial Community

Abstract: 1-Butyl-3-methylimidazolium chloride (BmimCl), an imidazolium-based ionic liquid, is considered the representative emerging persistent aquatic pollutant, and its environmental toxicity has attracted a growing concern. However, most of the investigations focused on monocultures or a single organism, with little information available on the complex syntrophic consortium that dominates the complex and successional biochemical processes, such as anaerobic digestion. In this study, the effect of BmimCl at environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…The maximum SCFA yield reached 290.3 ± 5.8 mg COD/g VSS in the 0.06 g/g TSS CTAB fermenter on day 8, while 0.09 and 0.12 g/g TSS CTAB fermentative groups obtained the highest SCFA yields of 262.4 ± 4.2 and 184.2 ± 5.4 mg COD/g VSS, respectively, on day 10. The reduction in the accumulated yield of SCFAs in fermenters with high doses of CTAB might be attributed to the inhibition of the activities of acid-producing bacteria by the high concentrations of chemicals . The SCFA yield decreased gradually after 10 days of fermentation, which might be caused by the rapid consumption of SCFAs by methanogens .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum SCFA yield reached 290.3 ± 5.8 mg COD/g VSS in the 0.06 g/g TSS CTAB fermenter on day 8, while 0.09 and 0.12 g/g TSS CTAB fermentative groups obtained the highest SCFA yields of 262.4 ± 4.2 and 184.2 ± 5.4 mg COD/g VSS, respectively, on day 10. The reduction in the accumulated yield of SCFAs in fermenters with high doses of CTAB might be attributed to the inhibition of the activities of acid-producing bacteria by the high concentrations of chemicals . The SCFA yield decreased gradually after 10 days of fermentation, which might be caused by the rapid consumption of SCFAs by methanogens .…”
Section: Resultsmentioning
confidence: 99%
“…The reduction in the accumulated yield of SCFAs in fermenters with high doses of CTAB might be attributed to the inhibition of the activities of acid-producing bacteria by the high concentrations of chemicals. 30 The SCFA yield decreased gradually after 10 days of fermentation, which might be caused by the rapid consumption of SCFAs by methanogens. 31 It was noteworthy that the SCFA yield of 0.06 g/g TSS CTAB fermenter (290.3 ± 5.8 mg COD/g VSS) was not significantly improved compared to the 0.03 g/g TSS CTAB reactor (273.5 ± 3.6 mg COD/g VSS).…”
Section: Yield Of Scfas During Was Fermentation Withmentioning
confidence: 99%
“…The adaptation of microorganisms in high-salinity environments (20 g/L NaCl) was explored by investigating the variations of bacterial and archaeal communities . It was found that at the phylum level, a high salinity significantly reduced the relative abundance of the phylum Euryarchaeota, which decreased from 48.77% to 18.26% after operation for 480 h. In contrast, the relative abundance of Firmicutes, Synergistetes, Thermotogae, and Actinobacteria increased, which were associated with accumulated VFAs in anaerobic digesters. , The promotion of these microorganisms might be due to the reduced relative abundance of methanogens and other functional microorganisms rather than an absolute increase in the number of bacteria associated with the production of VFAs. Additionally, these results also may be the microbial response to a salt shock.…”
Section: Responses Of the Microbial Community To Food Additives In Fo...mentioning
confidence: 99%
“…However, the influence of capsaicin on complex microbial systems (i.e., anaerobic fermentation system) has rarely been published. Anaerobic fermentation involves mainly substrates, microbes, and intricate biochemical reactions, namely, hydrolysis, acidification, and methanogenesis, each of which has the potential to become the rate-limiting step in the production of SCFAs . In this regard, it is imperative to discern the specific effects of capsaicin on each individual step in order to enhance our comprehension of the underlying mechanisms associated with the production of SCFAs.…”
Section: Introductionmentioning
confidence: 99%
“…Anaerobic fermentation involves mainly substrates, microbes, and intricate biochemical reactions, namely, hydrolysis, acidification, and methanogenesis, each of which has the potential to become the ratelimiting step in the production of SCFAs. 19 In this regard, it is imperative to discern the specific effects of capsaicin on each individual step in order to enhance our comprehension of the underlying mechanisms associated with the production of SCFAs. The systematic elucidation of microbial functional trait variations at the genetic level can provide insight into the influence of capsaicin on biological processes.…”
Section: Introductionmentioning
confidence: 99%